For a biblical regeneration of our Eucharistic practice - O'Loughlin, Thomas (Oriens Institute for Religious Research, 2018)
The church is semper reformanda: always in need of regeneration and renewal, not only of its ideas, but more importantly of its practices in order that it can become more fully what it is called to be: the voice and active presence of the Christ in the world. In this on-going task of regeneration, our practices surrounding the Eucharist are especially significant. As Hans Küng remarked in 2002: The liturgy is and remains the centre of the life of the church. If this can be successfully renewed, won’t that also have effects on all the areas of church activity?